Immobilization of laccase from Aspergillus oryzae on graphene nanosheets - Souza D.H.* (2017)
© 2017 Elsevier B.V.Laccase enzymes of Aspergillus oryzae were immobilized on graphene nanosheets by physical adsorption and covalent bonding. Morphological features of the graphene sheets were characterized via microscopy techniques. The immobilization by adsorption was carried out through contact between graphene and solution of laccase enzyme dissolved in deionized water. The adsorption process followed a Freundlich model, showing no tendency to saturation within the range of values used. The process of immobilization by covalent bonding was carried out by nitration of graphene, followed by reduction of sodium borohydride and crosslinking with glutaraldehyde. The process of immobilization by both techniques increased the pH range of activity of the laccase enzyme compared to the free enzyme and increased its operating temperature. On operational stability, the enzyme quickly loses its activity after the second reaction cycle when immobilized via physical adsorption, while the technique by covalent bonding retained around 80% activity after six cycles.